Delayed trigeminocardiac reflex induced by an intraorbital foreign body -: Case report - Yilmaz, T; Erol, FS; Yakar, H; Köhle, Ü; Akbulut, M; Ozveren, MF (Karger, 2006)
Objective: To emphasize the importance of the mechanism and surgical approach to trigeminocardiac reflex (TCR) developing 48 h after orbital trauma due to a foreign body. Case Report: After gunshot injury of a 17-year-old male patient, computerized tomography evaluation revealed a right globe perforation and an intraorbital metallic foreign body in the right orbita adjacent to the lateral wall. The ocular perforation was repaired, but the foreign body was not removed. Constant bradycardia (45/min) developed 48 h after the operation. Since there were no cardiological findings, a temporary cardiac pacemaker was inserted and on the 6th postoperative day, the foreign body was removed through orbitolateral approach. After the removal of the foreign body, bradycardia completely recovered. Conclusion: In the presence of an intraorbital foreign body accompanied by globe perforation, TCR may develop 48 h after the trauma and insertion of a temporary pacemaker may be required to control the cardiac rhythm. In this paper, the delayed TCR complication presented an indication for the removal of the intraorbital foreign body. Copyright (c) 2006 S. Karger AG, Basel.
Keywords: intraorbital foreign body; delayed bradycardia; pacemaker